The transformation of Japans security policy: Security identity under Shinzo Abe - Puzon, Jikko Alfonso Pradel (Animo Repository, 2016)
Japan made international headlines when its National Diet enacted the two controversial security bills which provide legal provision for the JSDF to operate more broadly and expand Japans freedom to provide logistical support to foreign militaries or defend the United States and other allies against an armed attack. Following significant security developments such as the reinterpretation of the Constitutions Article 9 and the establishment of Japans first National Security Council, the enactment of these security bills potentially mark a departure from Japans post-war security policy which is grounded in the Constitutions imposed pacifism and the country's domestic culture of antimilitarism. Scholars, specifically those under the realist tradition of international relations theory have interpreted these security developments as a reflection of Japan moving towards remilitarization or normalization. They believe that structural factors such as the military rise of China and the nuclear threat from North Korea have forced Japan to reconsider its foreign and security policy. This study challenges these accounts by arguing that the fundamental changes that the country is currently undergoing can be explained by a particular shift in Japans security identity which consequently reconfigured how the security policies of the state are processed. Instead of international structural factors, this study explores Japans security identity vis-à-vis the country's policymaking institutions in an attempt to shed light on the recent changes under the leadership of Prime Minister Shinzo Abe.